Peritraumatic dissociation predicts posttraumatic stress disorder symptoms via dysfunctional trauma-related memory among war-affected children - Peltonen, Kirsi (Eur J Psychotraumatol, 2017)
Background: Among adults there is strong evidence about peritraumatic dissociation (PD) predicting posttraumatic stress disorder (PTSD), yet evidence among children is very limited. It has been suggested that disturbances in memory functioning might explain the association between PD and PTSD, but this has not yet been empirically tested. Objective: We aimed to test the hypotheses that greater PD would be associated with more posttraumatic stress disorder (PTSD) symptoms, and that some of this association would be mediated by disorganized and non-verbal memories about the traumatic event. Method: The sample included 197 Palestinian children (10–12-years) living in the Gaza Strip, participating in the aftermath of the 2008/9 war. Self-report questionnaires were used to measure PD (Peritraumatic Dissociative Experiences Questionnaire) three months post-war, as well as trauma-related memory (Trauma Memory Quality Questionnaire) and PTSD symptoms (Children’s Revised Impact of Event Scale) six months later. Exposure to war trauma was assessed by a checklist. Structural equation modelling was used to examine direct and indirect paths from PD to posttraumatic PTSS, controlling for number of traumatic war events. Results: Structural equation modelling results showed that greater self-reported PD predicted higher levels of PTSS nine months post-war, and that a significant part, but not all, of this relationship was mediated via the quality of trauma-related memories. Conclusions: This study provided empirical evidence that, among war-affected children, greater PD during traumatic events is linked with higher levels of PTSD symptoms several months later, even when accounting for their personal exposure to war trauma. Further, the study supported the idea that the detrimental effects of dissociation during a traumatic event may be due to dysfunctional memories characterized by disorganization and lack of access to verbal and coherence. Further tests of these hypotheses with larger samples and more points of measurement are called for.